Mechanical Design of a 50 kg/hour Capacity Meat Grinder for Meatball Processing Using SolidWorks - Rahmatullah; Muhammad Rizky Ramadhiansyah; Arfis Amiruddin (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2026)
Abstract is a brief representation of the whole article which contains the context of the problem (background), the purpose of the research, the principal methods, the results and the major conclusion (contribution). An abstract is often presented separately from the article, so it must be able to stand alone. Thus, the reference must be avoided. Abstract must be written in Nunito , with no more than 300 words in one paragraph. The development of food processing machine designs and technologies that are appropriate, effective, and economical continues to be carried out. The same effort is applied to the development of meat grinding technology for household-scale, small business, and industrial meat processing. The meat grinding process aims to refine meat so that it can be processed into meatball products. Meat grinding machines have been developed by previous researchers with various capacities, such as 6 kg, 8 kg, 40 kg, and others. This meat grinding machine was designed using SolidWorks with dimensions of 506 mm × 305 mm × 705 mm. It has a relatively simple construction, is safe, and is easy to operate. The driving system of the meat grinder uses a 1 hp electric motor with a power output of 750 watts and a rotational speed of 2280 rpm. The meat grinding machine for meatball processing was designed with a capacity of 50 kg/hour. Based on the design results, it was found that the developed meat grinding machine has a relatively larger capacity compared to previous designs, more complete equipment components, and is easier to operate. In future research, this meat grinding machine will be developed with a PLC control system and based on the Internet of Things (IoT).